After the Move to a New Campus-Effects on Students' Satisfaction with the Physical and Learning Environment - Andreia P. Costa; Georges Steffgen (MDPI AG, 2020)
Few empirical studies in higher education consider the importance of the physical environment on students' satisfaction with the learning environment. The present study first examined the effects of a move to a new campus on students' satisfaction with the physical and learning environments. Then, it examined how students' satisfaction with a physical environment affects students' satisfaction with the learning environment. It was hypothesised that the move to a new and modern university campus with better study facilities would increase students' satisfaction both with the physical and learning environment, and that these two would be linked. Results contained 771 students' assessments of the Bachelor Evaluation Questionnaire, which included students' satisfaction with five aspects of their learning environment as well as five items assessing satisfaction with the physical environment. Findings showed that students were overall more satisfied with the physical environment in the new campus than in the old campus. These differences were even greater when comparing only students in their last study year than students of all study years. Furthermore, results showed that students' satisfaction with lecturers and teaching was predicted by increased satisfaction with classrooms. The implications of these findings for the need to design physical learning environments are discussed.